Evaluation of dynamic adsorption of dyes from aqueous solutions by applying mathematical modelling with the VS2TDI program and experimental studies - Liugė, Monika; Paliulis, Dainius (International Conference “Environmental Engineering”, 2023)
Dyes, heavy metals, sulphates, chlorides, petroleum products and other substances can be found in industrial wastewater. Synthetic dyes are divided into different groups according to their chemical composition. It is known that synthetic dyes have toxic and mutagenic properties. Adsorption is considered a reliable method for the removal of various pollutants. The adsorbent synthesized from paper waste, which has a lot of air gaps in its composition, is called aerogel. The maximum sorption capacity reached the value of 0.25–0.28 and 0.12–0.16 mg/g. It is characterized by low density and large surface area. Evaluation of dynamic adsorption of dyes from aqueous solutions was made by using the VS2TDI mathematical modelling program.